PECULIARITIES OF THE TEACHING OF THE SUBJECT "EDUCATION" IN THE PRIMARY SCHOOL - Jumatov Aydos Baxtiyar ulı (Ethiopian International Journal of Multidisciplinary Research, 2025)
The article deals with the introduction of practical approaches and effective pedagogical techniques in the teaching of younger pupils in the subject "Education" for the complete solution of educational and teaching tasks in the primary school.